Ex vivo tumor dissection followed by kidney autotransplantation in bilateral wilms tumor - Zhong, Zhihai; Jiang, Hong; Chen, Huadong; Wu, Chenglin; Wang, Yuanqi; Zhang, Zhichong; Li, Jun; Liu, Juncheng (Frontiers in Pediatrics, 2023)
Introduction Successful management of bilateral Wilm's tumor (BWT) involves a radical resection while preserving enough normal kidney tissue. Nephron-sparing surgery often results in an R1/R2 resection with a high recurrence rate in children with huge or multiple tumors, or tumors proximity to the renal hilum. In contrast, kidney autotransplantation can completely resect the tumor while maintaining homeostasis and preserving the patient's healthy kidney tissues. Methods We summarized the clinical data of 8 synchronous BWT patients who underwent kidney autotransplantation at the First Affiliated Hospital of Sun Yat-sen University from 2018 to 2020. Ex vivo tumor resection and kidney autotransplantions were performed on 11 kidneys. The baseline characteristics, perioperative management, and survival status were reported. Results Nephron-sparing surgeries were performed on 5 kidneys in vivo. Among all the 8 patients, six of them (75%) received staged operation and the other 2 patients (25%) received single-stage operation. No residual tumors were found on the postoperative imaging in all the 8 patients. In total, 6 (75%) patients occurred complications after the autotransplantation, among which, 2 (33.3%) patients had complication of Clavien-Dindo grade IIIa, and 4 (66.7%) patients had complication of grade < 3. During the 38 months of follow-up, 87.5% (7/8) of patients were tumor-free survival with normal renal function. One patient died from renal failure without tumor recurrence. Discussion Therefore, our study indicated that autologous kidney transplantation can be an option for patients with complex BWT if the hospital's surgical technique and perioperative management conditions are feasible.